2017
DOI: 10.1080/10872981.2017.1320187
|View full text |Cite
|
Sign up to set email alerts
|

Medical student resilience and stressful clinical events during clinical training

Abstract: Background: Medical students face numerous stressors during their clinical years, including difficult clinical events. Fostering resilience is a promising way to mitigate negative effects of stressors, prevent burnout, and help students thrive after difficult experiences. However, little is known about medical student resilience. Objective: To characterize medical student resilience and responses to difficult clinical events during clinical training. Design: Sixty-two third-year (MS3) and 55 fourth-year (MS4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
110
6
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 29 publications
10
110
6
7
Order By: Relevance
“…These conclusions are similar to those of a multicenter study that took place in five schools of medicine in the United States (Dyrbye et al, 2006). Furthermore, recently, Houpy et al (2017) concluded that a vast majority of the students who had experienced this syndrome had, for instance, family arguments which affected their welfare.…”
Section: Discussionsupporting
confidence: 79%
“…These conclusions are similar to those of a multicenter study that took place in five schools of medicine in the United States (Dyrbye et al, 2006). Furthermore, recently, Houpy et al (2017) concluded that a vast majority of the students who had experienced this syndrome had, for instance, family arguments which affected their welfare.…”
Section: Discussionsupporting
confidence: 79%
“…Third-year students have practicums and other classes that require them to acquire more specialized skills, and they were suggested to experience a higher level of school stress than fourth-year students. In particular, it has been reported that students in grades with clinical training should be stressful [26,27,28,29]. In the present study, there is clinical training in the third grade.…”
Section: Discussionmentioning
confidence: 57%
“…Students in clinical clerkship stage state that their health and quality of life are influenced by the difficulties encountered in clinical learning activities [6]. Education in the clinical clerkship stage needs to get attention because many students have a poor quality of life [7].…”
Section: Discussionmentioning
confidence: 99%